The Effect of Calorie Restriction on The Growth of Adipose Tissue in Mice - Hamda, Endanova Nur; Irwadi, Irfiansyah; Yuliawati, Tri Hartini (jitek, 2022)
The aging process can be slowed by reducing the calorie intake consumed by the body by calorie restriction or fasting. This study aimed to analyze the effect of calorie restriction on adipose tissue in mice. The experimental research design uses 12 months old Rattus Novergicus Strain Wistar, weighing 250–300 grams. The intervention was carried out for 14 days, then the average weight of subcutaneous and visceral fat was measured using Kruskal Wallis analysis and ANOVA. Based on the four treatment groups, the mice fasting and given a high-calorie diet (group 4) had the highest average fat weight value of 4.02 grams in the subcutaneous and 3.55 grams in the visceral area. Meanwhile, in group 1, mice that were not fasting and did not get a high-calorie diet had the lowest average fat weight values, namely 2.14 grams in the subcutaneous area and 2.72 grams in the visceral area. Based on the test results, it was found that there was no difference between subcutaneous (p=0.121) and visceral (p=0.443) fat tissue in all groups. Calorie restriction is beneficial for delaying aging and increasing mammal life span, but intermittent calorie restriction does not affect adipose tissue.